Autophagy in the corpus luteum correlates with tissue growth in pregnant rats - Yasuaki OISHI; Koji ASAKAWA; Yuri ISHIWATA; Shota OKA; Ryota TERASHIMA; Makoto SUGIYAMA; Keiichiro KIZAKI; Mitsumori KAWAMINAMI; Shiro KURUSU (The Society for Reproduction and Development, 2024)
The developmental activation of the corpus luteum (CL) structurally and functionally is critical for the temporally regulated establishment, maintenance, and termination of pregnancy in rats. In this study, we have investigated the possible involvement of autophagy in the regulation of the CL during pregnancy in rats. The expression ratio of microtubule-associated protein light chain 3 (LC3)-II/-I, a widely used indicator of autophagic activity, in the CL remained relatively stable until day 15 of pregnancy. Subsequently, it progressively increased until day 21, and then declined until day 3 postpartum. This fluctuation was closely associated with the tissue weight of the CL rather than progesterone (P4) production activity. Light and electron microscopy revealed the presence of immunoreactive LC3 aggregates and irregularly shaped autolysosome-like microstructures in the cytoplasm of luteal cells during late pregnancy. Notably, a bolus intrabursal injection of the autophagy inhibitor bafilomycin A1 on day 15 of pregnancy resulted in a significant reduction in luteal cell size and disrupted the normal alteration of circulating P4 levels. Consequently, treatment with this inhibitor increased the likelihood of the varied timing (both advanced and delayed) of delivery and led to reduced body weight in neonates when compared with the vehicle-treated control group. Our findings suggest that autophagy in the rat CL contributes to luteal tissue growth, influences P4 production, and thereby fine-tunes the regulation of gestation length in rats.